2007
DOI: 10.1124/jpet.107.131615
|View full text |Cite
|
Sign up to set email alerts
|

The Guinea Pig as a Preclinical Model for Demonstrating the Efficacy and Safety of Statins

Abstract: Statins, because of their excellent efficacy and manageable safety profile, represent a key component in the current armamentarium for the treatment of hypercholesterolemia. Nonetheless, myopathy remains a safety concern for this important drug class. Cerivastatin was withdrawn from the market for myotoxicity safety concerns. BMS-423526 ,5-dihydroxy-heptenoic acid} sodium salt], similar to cerivastatin in potency and lipophilicity, was terminated in early clinical development due to an unacceptable myotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…In the guinea pig, skeletal muscle concentrations of rosuvastatin and atorvastatin are less than 10% of that found in plasma, suggesting that the balance is tipped toward higher efflux than uptake activity. 60 In our evaluation of the literature, the plasma-to-skeletal muscle concentration ratio of statins in humans is not known, but this value will undoubtedly be dependent on the relative expression and intrinsic activities of the attendant uptake (OATP2B1) and efflux (MRP1, MRP4, MRP5) transporters. The present results would also suggest that drug-statin interactions occurring not only at the level of the hepatocyte cell membrane but also in skeletal muscle fibers could contribute to myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the guinea pig, skeletal muscle concentrations of rosuvastatin and atorvastatin are less than 10% of that found in plasma, suggesting that the balance is tipped toward higher efflux than uptake activity. 60 In our evaluation of the literature, the plasma-to-skeletal muscle concentration ratio of statins in humans is not known, but this value will undoubtedly be dependent on the relative expression and intrinsic activities of the attendant uptake (OATP2B1) and efflux (MRP1, MRP4, MRP5) transporters. The present results would also suggest that drug-statin interactions occurring not only at the level of the hepatocyte cell membrane but also in skeletal muscle fibers could contribute to myopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we chose similar doses (10 and 20 mg/kg) and a lower dose (1 mg/kg) of PPs. The atorvastatin dose of 80 mg/kg and the treatment regimen for 16 days were in the mid range of values in the literature (Madsen et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Probiotics are beneficial bacteria that influence the health of the host by improving their microbial balance. Modifications of intestinal flora have been shown to be beneficial on lipid metabolism in mice [2][3][4][5][6], rats [7][8][9][10][11], guinea pigs [12] and pigs [13]. In contrast, studies in humans [14,15] indicated that the role of fermented milk products as hypocholesterolaemic agents were inconsistent but more reliable effects were documented in the recent clinical studies [16][17][18][19].…”
Section: Introductionmentioning
confidence: 95%